Determination of dust and microorganism accumulation in different designs of AHU system in Shaanxi History Museum. (1st August 2016) - Li, Angui; Xiong, Jing; Yao, Lingzhi; Gou, Li; Zhang, Wenrong
Abstract: Serial environmental measurements were conducted in the Shaanxi History Museum with two different air handling unit (AHU) designs to obtain a distribution of airborne and dust-borne microorganisms, and to determine the effects of occupant density, temperature and relative humidity (RH) on airborne or dust-borne microbial counts. Samples were collected from five segments of three AHU systems during 9:00–10:00 and 15:00–16:00. The results indicated that a high density of occupants caused a serious accumulation of airborne bacteria and fungi regardless of whether the system was a constant air volume (CAV) or variable air volume (VAV) system. In both of the aforementioned systems, the same downward trend in airborne bacterial counts was observed, where the highest counts were found at the return air segment, followed by the filter and supply air segments. Nevertheless, airborne fungal counts showed opposing trends in CAV and VAV systems. Our results also demonstrated that dust loading in the VAV system was in the range of 1.1–13.3 g/m 2 which meets the Chinese standard, while dust-borne bacterial counts (4.6 × 10 4 –36.9 × 10 4 CFU/gdust ) and fungal counts (5.3 × 10 4 –1129 × 10 4 CFU/gdust ) far exceeded relevant threshold value. Furthermore, dust loading was more closely correlated with dust-borne bacteria levels than dust-borne fungi levels. In addition, airborne or dust-borne fungal counts were higher than the bacterial counts in the same sampling locations in the two systems. The predominant fungal genera that were consistently identified in different segments of both CAV and VAV systems were Penicillium, Aspergillus and Cladosporium . Moreover, RH exerted a greater influence on microbial growth than temperature. Graphical abstract: Highlights: CAV and VAV systems had different influence on airborne fungi, respectively. Airborne bacterial counts showed downward trends both in CAV and VAV system. Airborne fungal counts showed downward trend in CAV while upward in VAV system. Microbial counts may exceeded threshold value even if dust loadings met criterion. The fungal genera were remarkably consistent among different systems or segments.